A Correlational Study Between Listening Comprehension And Students’ Listening Preference - Purnamasari, Purnamasari; Sailan, Zalili; Sartiah, Sartiah (Halu Oleo University, 2016)
This study investigated the correlation between listening comprehension and students’ listening preference at the first year of English Study Program of Halu Oleo University. It aimed of finding out the correlation of listening comprehension and listening preference in between and the correlation between listening preference and students’ gender. Samples were 44 students drawn using a random sampling technique. Instrument of the study were multiple choices tests of IELTS and TOEFL consisting of 20 items each of them, which was used to measure students’ listening comprehension, and a questionnaire featuring 14 items to gauge students’ listening preference towards British and American English. Data were analyzed using descriptive statistic and correlation analysis. Results showed that listening comprehension has a positive correlation toward listening preference and there is no correlation between students’ listening preference and their gender because both male and female have high score in TOEFL test and they prefer American to British English. Since the study did not investigating the most influence factor of listening comprehension, the researcher recommended that future researchers to investigate the factor.